Focusing on Paul: Persuasion and Theological Design in Romans and Galatians - Du Toit, Andreas B. (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2007)
Biographical note: Andriedu Toit, University of Pretoria, South Africa; Cilliers Breytenbach, Humboldt University,Berlin, Germany,andUniversity of Stellenbosch, South Africa; David S. du Toit, Humboldt University,Berlin, Germany.